VISIÓN FENOMENOLÓGICA DE LA LECTURA DIGITAL CREATIVA COMO ELEMENTO DE TRASCENDENCIA PARA LA RESOLUCIÓN DE CONFLICTOS ESCOLARES (De la Crítica, 2024)
The teacher plays an important role within educational institutions, such as mediator in resolving conflicts that arise within the school. For this reason, the purpose of this research work was to generate the theoretical construct of creative digital reading as an important element for the resolution of conflicts in the classroom, as a study perspective from Gadamer's phenomenology. The Paradigm assumed in the research is the interpretative one proposed by Martínez. (2013), the qualitative method of Hernández, Fernández and Batista (2008); Observation and interviews are used as analysis techniques and instruments, while categorization and triangulation are used for analysis. In this case, the key informants are made up of 3 teachers from the educational institution: who provided the necessary elements for the process of understanding and interpreting the information. The results obtained show that creative digital reading as an emerging trend is a mechanism that In the case of the school, it contributes to the teacher acting as a mediator for the solution of specific situations, promoting in young people the ethical, moral and social values that allow them to function in society and promote an environment of peace and healthy coexistence.